2013
DOI: 10.1007/s13238-013-3062-5
|View full text |Cite
|
Sign up to set email alerts
|

CD1dhiCD5+ B cells differentiate into antibody-secreting cells under the stimulation with calreticulin fragment

Abstract: Calreticulin (CRT) is a multifunctional molecule in both intracellular and extracellular environment. We have previously found that a recombinant CRT fragment (rCRT/39-272) could modulate T cell-mediated immunity in mice via activation and expansion of CD1d(hi)CD5⁺ B cells as well as induction of CRT-specific regulatory antibodies. Antibody secreting cells (ASCs) are terminally differentiated B cells responsible for producing antibodies to participate in positive immune response as well as immune regulation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As one of the HSPs, soluble CRT protein exhibits potent immunological functions both in vivo and in vitro , such as activating monocytes/macrophages and expanding CD1d hi CD5 + B10 cells [ 13 16 ]. Given that elevated levels of soluble CRT in body fluids (serum and synovial fluid) correlate with autoimmune disease and cancer in humans, immunobiological activities of CRT deserves detailed investigation.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the HSPs, soluble CRT protein exhibits potent immunological functions both in vivo and in vitro , such as activating monocytes/macrophages and expanding CD1d hi CD5 + B10 cells [ 13 16 ]. Given that elevated levels of soluble CRT in body fluids (serum and synovial fluid) correlate with autoimmune disease and cancer in humans, immunobiological activities of CRT deserves detailed investigation.…”
Section: Resultsmentioning
confidence: 99%
“…HSP70), and high-mobility group I (HMGB1) protein [20]. Recombinant CALR fragment was shown to exhibit potent stimulatory activities against B cells [21, 22]. Recently, we reported that activated B cells are increased in ET patients, and can facilitate platelet production mediated by cytokines, such as interleukin (IL)-1β and IL-6 regardless JAK2 V617F mutational status [23].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils secrete azurocidin, which has been shown to bind to CALR and induce cytokine production in monocytes ( 124 ). A partial recombinant CALR fragment from mice was found to stimulate human monocytes and B cell cytokine secretion ( 125 ), as well as stimulate B cell differentiation into antibody secreting cells ( 126 ). Interestingly, stimulation of macrophages with recombinant CALR induced expression of TNFα and IL-6.…”
Section: Calreticulin Effects On Immune Cell Responsementioning
confidence: 99%